ADAPTATION STRATEGY OF MOSQUE ARCHITECTURE IN THE MINORITY NEIGHBORHOOD Case Studies: Mosques in Denpasar City and Badung Regency, Province of Bali. - Saputra, Andika; Rochis, Muhammad (Journal of Islamic Architecture, 2014)
Mosque for Muslims who living in the middle of minority neighborhood in Province of Bali not only function as a signifier for the presence a Muslims community, but also have a central role because mosque is the only gathering place for fellow Muslims. In the present, Muslims in the province of Bali is facing various challenge that cause adaptation strategies of mosque architecture for the existence of mosque in the neighborhood can be accepted by society from other faith. This preliminary study aim to knowing the adaptation strategies of mosque architecture undertaken Muslims in the province of Bali along with the factor that drive adaptation. Study conducted using qualitative-inductive method. Locus of study in the Denpasar City and Badung Regency where is the center of activity and concentration of Muslims in the province of Bali with a different background neighborhood. Object of study used a large mosque that are the central of Muslims activity. The finding this study showed that there are three types of mosque architecture adaptation strategies undertaken by Muslims in the Province of Bali are (1) external factor are responded by applying dominate elements of Balinese style architecture, (2) internal factor is awareness to applying elements of Balinese style architecture to show identity as a Muslims who appreciate local value, and (3) internal factor to applying the characteristic architectural style of the Middle East mosque is considered ideal to represent identity as Muslims.